Black boys matter – A Black supplementary school's approach to supporting SEMH needs. Issue 3 (7th November 2022) - Ricketts, Laura; Kambouri, Maria; Majors, Karen
The birth of Black Supplementary Schools (BSSs) in the 1960s was a socio-political movement. They sought to reduce the failings of Black children in the mainstream education system by offering them additional learning spaces. However, there is limited research on their functionality and how they support children with Special Educational Needs (SEN), such as Social, Emotional and Mental Health (SEMH). This study sought to shed light on the role a BSS played in supporting Black boys who had been labelled with challenging behaviour by their mainstream educational provision and were at risk of or had been permanently excluded. The research adopted a single case-study design, employing qualitative data collection using semi-structured interviews. Thematic analysis was used to analyse the data; five main themes found were 'Education is more than academia', 'Strong sense of belonging', 'People empowerment through unique opportunities', 'Knowing and growing thy self' and 'Supporting systemic strategies'. The recent insurgence of 'Black Lives Matter' highlighted that racial inequalities remain deeply embedded within the structural mechanisms of society. This research sheds light on the ways in which BBS's support Black children to succeed educationally. Moreover, there are further implications for education settings, educators and other education professionals including Educational Psychologists.